Gold Nanoparticle-Decorated Polymer Particles for High-Optical-Density Immunoassay Probes - Yabu, Hiroshi (Langmuir : the ACS journal of surfaces and colloids, 2024)
To realize a highly sensitive immunoassay, high-optical-density probes conjugated with antibodies for target antigens are needed to increase the detectability of antigen-antibody complex formation. In this work, gold nanoparticle (NP)-decorated polymer (GNDP) particles were successfully prepared by mixing positively charged polymer particles and negatively charged Au NPs. GNDP particles decorated with NPs of 20 nm in size had higher optical density than the original Au NPs and GNDPs decorated with smaller Au NPs. Using GNDP particles as a probe, a highly sensitive immunoassay for influenza H1N1 hemagglutinin was realized with a minimum detectable concentration of 32.5 pg/mL. These results indicate that GNDP particles have high potential as an immunoassay probe that can be used in practical immunoassay systems for detecting a wide variety of antigens